2005
DOI: 10.1016/j.ymthe.2004.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Lentivirus-mediated gene transfer induces long-term transgene expression of BMP-2 in vitro and new bone formation in vivo

Abstract: We examined the potential of ex vivo gene therapy to enhance bone repair using lentiviral vectors encoding either enhanced green fluorescent protein (EGFP) as a reporter gene or bone morphogenetic protein-2 (BMP-2) downstream of either the cytomegalovirus immediate early (CMV) promoter or the murine leukemia virus long terminal repeat (RhMLV) promoter derived from a murine retrovirus adapted to replicate in a rhesus macaque. In vitro, rat bone marrow stromal cells (BMSCs) transduced with Lenti-CMV-EGFP or Lent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
94
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(99 citation statements)
references
References 54 publications
5
94
0
Order By: Relevance
“…(iii) Gene expression with lentiviral vectors can effectively be achieved in hMSCs (Totsugawa et al, 2002) and continuous stable gene expression was demonstrated throughout differentiation (Sugiyama et al, 2005). (iv) Functional RNA interference in hMSCs throughout differentiation is well documented (Hoelters et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…(iii) Gene expression with lentiviral vectors can effectively be achieved in hMSCs (Totsugawa et al, 2002) and continuous stable gene expression was demonstrated throughout differentiation (Sugiyama et al, 2005). (iv) Functional RNA interference in hMSCs throughout differentiation is well documented (Hoelters et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Expression of matrix proteins, such as AMBN, offers the possibility to study their function and possible application in the development of novel strategies for bone regeneration. In addition, because lentiviruses can sustain expression of a transgene over periods of several months, 29,30,34,49 they can be advantageously exploited for rescue experiments in knockout mice with canonical and mutated proteins. …”
Section: Discussionmentioning
confidence: 99%
“…28 Efficient lentivirus-mediated gene transfer has been demonstrated in several cells and tissues, including skeletal muscle, 29 salivary glands, 30 liver, 29 neural tissues 31,32 and keratinocytes. 33 There are only few studies on the administration of lentiviral vectors (LVs) at calcified tissue sites and these dealt with the periosseous implantation of cells infected ex vivo 21,34 and local injection of the vector into the synovium. 10,35 Local delivery of viral vectors into bone remains problematic because it has so far been limited to readily accessible anatomical sites such as the synovial cavity and bone defects, and relatively large amounts of vector and its local persistence are required to successfully infect a sufficient number of cells.…”
Section: Introductionmentioning
confidence: 99%
“…Gene transfer could overcome these limitations. Several viral vectors carrying BMP-2 cDNA have been studied on animal models over the years [4,5,104]. All showed promising results for future clinical application.…”
Section: Injection Of Growth Factors For Enhancement Of Fracture Healingmentioning
confidence: 99%